High resolution computed tomography findings in smear-negative pulmonary tuberculosis patients according to their culture status - Tayfun, Caliskan; Ozkisa, Tuncer; Aribal, Serkan; Kaya, Hatice; Incedayi, Mehmet; Ulcay, Asim; Ciftci, Faruk (Journal of Thoracic Disease, 2014)
Objective: The aim of this study was to assess the clinical features and high resolution computed tomography (HRCT) findings in smear-negative pulmonary tuberculosis (PTB) and to evaluate the correlation between these parameters and the culture results. Methods: We retrospectively studied 78 active smear-negative PTB patients. They were divided into two groups according to their culture results. The HRCT findings and clinical features at the beginning of the antituberculosis treatment were reviewed. Results: The mean age was 22.48±3.18 years. Micronodules (87%), large nodules (63%) and centrilobular nodules (62%) were the most common HRCT findings. HRCT findings were observed in the right upper (72%), left upper (56%), right lower (32%), and left lower lobes (29%). Cough (37%) and chest pain (32%) were the most frequent symptoms at presentation. Conclusions: There were no significant differences in the HRCT findings and clinical features between the two groups. Thus, in cases of smear-negative and culture-negative PTB, the patient with compatible clinical and radiological features should be considered for tuberculosis treatment.